Search complementarities, aggregate fluctuations, and fiscal policy - Jesús Fernández-Villaverde; Federico S. Mandelman; Yang Yu; Francesco Zanetti (Federal Reserve Bank of Atlanta, 2019)
We develop a quantitative business cycle model with search complementarities in the inter-firm matching process that entails a multiplicity of equilibria. An active equilibrium with strong joint venture formation, large output, and low unemployment coexists with a passive equilibrium with low joint venture formation, low output, and high unemployment. Changes in fundamentals move the system between the two equilibria, generating large and persistent business cycle fluctuations. The volatility of shocks is important for the selection and duration of each equilibrium. Sufficiently adverse shocks in periods of low macroeconomic volatility trigger severe and protracted downturns. The magnitude of government intervention is critical to foster economic recovery in the passive equilibrium, while it plays a limited role in the active equilibrium.
Keywords: C63; C68; E32; E37; E44; G12; 330; aggregate fluctuations; strategic complementarities; macroeconomic volatility; government spending